Lifestyle cities, remote work and implications for urban planning. Issue 1 (3rd April 2022) - Zenkteler, Matthew; Foth, Marcus; Hearn, Gregory
ABSTRACT: Australia's cities and regions are the envy of the world for their natural beauty and lifestyle amenities and attractions. Not only has this sustained the tree-change and sea-change movement, with broadband connectivity and the COVID-19 pandemic so-called 'e-changers' and 'flee-changers' are part of the populus seeking to combine career aspirations with lifestyle destinations. This paper discusses the growing popularity of remote, particularly home-based work, and planning and design responses that accommodate this type of work in residential neighbourhoods. The issues are exemplified through a case study of the City of Gold Coast drawing on mixed methods including survey instruments and a design charrette facilitated by the authors. The design charrette is reported via three integrative narratives of a remote worker, the neighbourhood and the city. Findings outline preferences of remote workers towards built environment and urban design features enabling collaboration and knowledge exchange and assist in a better understanding of the socio-economic factors behind the spatial distribution of home-based work. The study's findings offer a range of implications for appropriate urban planning and design responses.